Investigating persuasive strategies used in Zakir Naik’s Islamic lecture at Oxford Union - Alida, Rizky; Budiwati, Tri Rina; Fatimah, Nur; Afifah, Wiwiek (EduLite: Journal of English Education, Literature and Culture, 2024)
Islamic lectures are potent media for people to influence others, specific groups, and society. Based on this case, this research aims to identify and analyze the types of persuasive strategies used by Zakir Naik in his Islamic Lecture under the theme “Islam and the 21st Century,” which took place at the Oxford Union. This descriptive and qualitative research used the Critical Discourse Analysis (CDA) approach proposed by Teun A. Van Dijk. Furthermore, Aristotle’s Rhetorical Theory of Persuasion was employed to support the analysis of how persuasive strategies were applied in the Islamic lecture. The data of this research were the sentences of the speech text transcription, which contained persuasive strategies spoken by Zakir Naik in his “Islam and the 21st Century” Oxford Union Islamic Lecture uploaded on his YouTube Channel. The results show three categories of “socio-cognitive” CDA by Teun A. Van Dijk, namely, text, cognition, and social context, which are used to analyze the speech text and its relation to social and power. Concerning this, the persuasive strategies analysis shows that Zakir Naik uses three types of rhetorical proofs from a total of 121 data, which include ethical proof (ethos), logical proof (logos), and emotional proof (pathos). Ethos is the most common rhetorical proof in his Islamic lecture, making up 63.5% of the speech. It is followed by pathos (33.58% of the speech) and logos (27.22% of the speech).